2017
DOI: 10.1097/mph.0000000000000778
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus for Treatment of Pseudomyogenic Hemangioendothelioma

Abstract: Pseudomyogenic hemangioendothelioma (PMH) is a recently described vascular neoplasm that occurs most commonly in the soft tissue of the distal extremities of young adults. Metastatic PMH can be fatal and there are no effective medications. We describe a case of a 15-year-old boy with metastatic PMH, who responded to treatment with everolimus, a mammalian target of rapamycin inhibitor. Immunohistochemistry showed that mammalian target of rapamycin was expressed in PMH biopsy specimens, which may explain the red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 18 publications
1
32
0
Order By: Relevance
“…Different systemic therapies have been described in case reports present in literature. The mammalian target of rapamycin inhibitors (mTOR), like sirolimus and everolimus, have demonstrated the major efficiency (Table ; Jason et al, ; Gabor et al, ; Ozeki et al, ; van IJzendoorn et al, ; Stuart et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different systemic therapies have been described in case reports present in literature. The mammalian target of rapamycin inhibitors (mTOR), like sirolimus and everolimus, have demonstrated the major efficiency (Table ; Jason et al, ; Gabor et al, ; Ozeki et al, ; van IJzendoorn et al, ; Stuart et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, over a third of patients show local relapses after surgery (Jason et al, 2015). (Table 1; Jason et al, 2015;Gabor et al, 2018;Ozeki et al, 2017;van IJzendoorn et al, 2018;Stuart et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that SKP2 is an important oncogene in many types of cancer, a negative regulator of the mTOR complex and can thereby be targeted by mTOR inhibitors [11‐13]. Reported literature demonstrated that the mTOR inhibitor has achieved satisfactory results in treating chemo‐resistance PHE cases [7‐10]. As mentioned above, case 1 received everolimus treatment which produced a notable local maintenance effect.…”
Section: Figurementioning
confidence: 93%
“…In 13 patients with available adjuvant treatment data, 5 (38.5%) patients had disease that progressed after chemotherapy or radiotherapy (Supplementary Table 2). In contrast, 3 chemoresistant PHE cases achieved promising results after target therapy [7‐10]. Therefore, this suggests that targeted therapy seems to more beneficial than traditional treatment in PHE.…”
Section: Figurementioning
confidence: 99%
“…Two patients (3%) developed regional lymph node metastasis. 3,12 Recently, the use of targeted therapy with mammalian target of rapamycin inhibitors, specifically, everolimus 25 and sirolimus, 26 in children aged 15 and 9 years, respectively, was attempted, with promising results. Everolimus was also used in a 22-year-old patient for 2 months and showed mild shrinkage of the tumors.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%